Subdividing Extension of Eulerian Graphs - Attar, Akram B.; Alwan, Alyaa A. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, the subdividing extensibility number for Eulerian graphs has been studied. Eulerian graphs with subdividing extensibility number at most 3 are characterized.
Keywords: Eulerian Graphs; Extension of Graphs; Reconstruction of Graphs